Identification of a Glycoprotein III a Dimer in Polyacrylamide Gel Separations of Human Platelet Membranes - Calvete, J J; McGregor, J L; Rivas, G; González-Rodríguez, J (Thrombosis and Haemostasis, 1987)
Membrane glycoproteins IIb and IIIa play a major role in human blood platelet aggregation. The absence or the severe reduction of these two membrane glycoproteins, as observed in platelets of Glanzmann’s thrombasthenic patients, is related to a lack of platelet aggregation. Separation of Glanzmann’s thrombasthenic platelet samples by two-dimensional polyacrylamide O’Farrell gels show the absence of a high and several low molecular mass glycoproteins, in addition to the loss of glycoproteins IIb and IIIa (McGregor J. L. et al. Eur. J. Biochem. 1981; 116: 379-388). The aim of this study was to identify the nature of the high molecular mass component, absent in thrombasthenic platelets. A high molecular mass glycoprotein (200 kDa), present in two-dimensional SDS-polyacrylamide O-Farrell gel separations, was recognized by a monoclonal antibody (MP37) directed against glycoprotein IIIa. Moreover, the tryptic peptide map of this high molecular mass glycoprotein was nearly identical to that of glycoprotein IIIa. These results indicate that this high molecular mass glycoprotein present in SDS-polyacrylamide gels is a dimer of glycoprotein IIIa. This work raises the possibility that the high molecular mass glycoprotein, absent in two-dimensional O’Farrell gel separations of thrombasthenic platelets, is a dimer of glycoprotein IIIa.
Keywords: Platelets; Glycoprotein IIIa; Glycoprotein IIIa dimer; Tryptic peptide maps; Monoclonal antibody MP37